2001
DOI: 10.1016/s0014-5793(00)02333-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the main ubiquitination site in human erythroid α‐spectrin

Abstract: Erythroid spectrin is the main component of the red cell membrane skeleton, which is very important in determining the shape, resistance to mechanical stresses and deformability of red cells. Previously we demonstrated that human erythroid K K-spectrin is ubiquitinated in vitro and in vivo, and using recombinant peptides we identified on repeat 17 the main ubiquitination site of K K-spectrin. In order to identify the lysine(s) involved in the ubiquitination process, in the present study we mutated the lysines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Some structural preferences exist for ubiquitin ligation of the targeted proteins such as preferred choice of lysines in α-helices, and then for easily accessible lysines in the loop regions. Our findings add to the growing list that indicates a bias towards a consensus sequence motif for ubiquitination by a given E3 [19][20][21][22][23][24][25]. Moreover, it appears that the E3 targets an accessible surface residue providing the selection process with a conformational recognition mechanism.…”
Section: Receptor Ubiquitination Implicated In Regulation Of Trkb Dowsupporting
confidence: 52%
“…Some structural preferences exist for ubiquitin ligation of the targeted proteins such as preferred choice of lysines in α-helices, and then for easily accessible lysines in the loop regions. Our findings add to the growing list that indicates a bias towards a consensus sequence motif for ubiquitination by a given E3 [19][20][21][22][23][24][25]. Moreover, it appears that the E3 targets an accessible surface residue providing the selection process with a conformational recognition mechanism.…”
Section: Receptor Ubiquitination Implicated In Regulation Of Trkb Dowsupporting
confidence: 52%
“…It is possible that the association of ␣-and ␤-Spectrin blocks ubiquitination of ␣-Spectrin and its subsequent degradation via the proteasome. Ubiquitination has been previously reported for ␣-Spectrin (Corsi et al, 1995;Galluzzi et al, 2001) and may thus help to define the correct protein-expression levels.…”
Section: Discussionmentioning
confidence: 80%
“…The erythrocyte AE1 interacts with protein 4.1, ankyrin and spectrin, which comprise the erythrocyte cytoskeleton, and the importance of the interactions in the shape maintenance and deformability of erythrocytes is well-established (Walensky et al, 1998;Galluzzi et al, 2001;An et al, 2005). Recent studies have indicated that the cytoskeleton in nucleated cells provides mechanical support to the cell plasma membrane, and cytoskeletal networks are present in various intracellular structures that are involved in the regulation of major cellular functions, such as morphogenesis, cell proliferation, cell migration and cell-cell contact (Gascard and Mohandas, 2000;Takakuwa, 2000;Durham and Herman, 2009).…”
Section: Discussionmentioning
confidence: 99%